Integrating digital health into pediatric obesity management: Current practices and future perspectives - Vittoria Frattolillo; Alessia Massa; Dalila Capone; Noemi Monaco; Gianmario Forcina; Pierluigi Di Filippo; Pierluigi Marzuillo; Emanuele Miraglia del Giudice; Anna Di Sessa (Obesity Pillars, 2025)
Background: Childhood obesity is a growing global health concern with significant cardiometabolic consequences. While conventional treatment approaches often fail to achieve sustained outcomes, emerging digital health interventions (DHIs)—including mobile applications, educational video games, wearable devices, telemedicine, and social media—offer innovative tools to support lifestyle modifications and enhance therapeutic adherence. Methods: In this narrative review, we focus on the main evidence regarding the effectiveness of DHIs for pediatric obesity treatment according to target (children vs. children with families) and duration (short- and long-term interventions). We also review their impact on clinical (e.g. body mass index, body composition, etc.), behavioral (physical activity, nutrition, adherence) and psychosocial (motivation, engagement) outcomes. In addition, future trends in the field are also discussed. Results: DHIs demonstrate short-term effectiveness, especially when they incorporate personalization, interactivity, and family involvement. Mobile applications and educational video games boost nutritional literacy and promote healthy behaviours. Wearable devices encourage physical activity awareness, though adherence often varies. Long-term, family-based interventions help reduce dropout rates and reinforce lasting healthy habits. Guided use of social media can facilitate health education but also exposes users to risks such as misinformation and unhealthy food marketing. Despite these advancements, DHIs still face major challenges, including unequal access, data privacy concerns, and a lack of long-term outcome evaluations. Conclusion: The increasing prevalence of pediatric obesity underscores the urgent need for effective and sustainable treatment strategies. DHIs represent a promising, scalable approach for managing childhood obesity, but their long-term sustainability and effectiveness remain to be fully established. Ongoing technological advancements—and their thoughtful integration into existing healthcare frameworks—present significant opportunities to develop innovative, patient-centered therapeutic solutions that can improve engagement, adherence, and long-term health outcomes in children and adolescents with obesity.